Улс төрийн намын институцжилт: онолын асуудалд - С.МӨНХБАТ (Politology, 2017)
The political parties play an important role to foresee and overcome the barriers which happened during the democratic transition. The party must be the political organization, which implements the democracy. In this article presents how party organize? and party institutionalization’s theories in the party studies. Here, I made a conclusion that it is related to subordinating organization pattern of political parties in certain places.